Nivel de conocimiento sobre tratamiento de complicaciones postquirúrgicas de exodoncias simples según ciclo de estudios en la facultad de odontología–UNAP - Vela Rodriguez, Lucas Augusto (2023)
The purpose of the study was to evaluate the degree of knowledge of dental students about the treatment of local postsurgical complications of simple exodontia. Quantitative study of non-experimental, cross-sectional, correlational design; with a sample of 140 students enrolled and active in the second semester of the year 2022, of the cycles in which they are taking or have been taking the course of oral surgery or oral-maxillofacial surgery. The instrument used was a questionnaire of questions, grouped in three categories, low/bad - medium/regular - high/good. The instrument was a 12-question questionnaire. The results showed that the knowledge about treatment of post-surgical complications of simple exodontia according to the cycle of studies in the dental school was medium with 65%, low with 28.6% and high with 6.4% in total of all the cycles. With respect to each cycle in particular, VI 71.4%, VIII 61.7%, X 66.7%, XII 57.1% leaving the sixth cycle as the one with the highest percentage of MEDIUM knowledge. It is concluded that the medium level of knowledge presented the highest percentage in all the cycles.